2017
DOI: 10.1111/jcpp.12725
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial to test the effect of promoting caregiver contingent talk on language development in infants from diverse socioeconomic status backgrounds

Abstract: A social gradient in children's communication emerges during the second year of life. A low-intensity intervention demonstrated that it is possible to increase caregiver contingent talk and that this is effective in promoting vocabulary growth for lower SES infants in the short term. However, these effects are not long-lasting, suggesting that follow-up interventions may be necessary to yield benefits lasting to school entry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
123
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(127 citation statements)
references
References 49 publications
3
123
0
1
Order By: Relevance
“…was coded based on linguistic context and, when available, visual context, it's possible that indistinguishable object presence across video and peak audio is due to a combination of noise and systematic bias in coding object presence without visual context. Because object presence and the related ideas of referential transparency and contingent talk have been linked with early language development based on both audio-only and video-recordings(Bergelson & Aslin, 2017;Cartmill et al, 2013;McGillion, Pine, Herbert, & Matthews, 2017;Yurovsky et al, 2013), we find this latter possibility somewhat unlikely. Indeed, a better understanding of what elicits contingent, referentially transparent caretaker talk may be a fruitful future direction.…”
mentioning
confidence: 80%
“…was coded based on linguistic context and, when available, visual context, it's possible that indistinguishable object presence across video and peak audio is due to a combination of noise and systematic bias in coding object presence without visual context. Because object presence and the related ideas of referential transparency and contingent talk have been linked with early language development based on both audio-only and video-recordings(Bergelson & Aslin, 2017;Cartmill et al, 2013;McGillion, Pine, Herbert, & Matthews, 2017;Yurovsky et al, 2013), we find this latter possibility somewhat unlikely. Indeed, a better understanding of what elicits contingent, referentially transparent caretaker talk may be a fruitful future direction.…”
mentioning
confidence: 80%
“…Tier 1 services also focus on children before they enter education and often aim to change parents' interaction with their children, to increase the amount of contingent talk (McGillion et al 2017, Landry et al 2011 or increase the vocabulary children are exposed to, e.g., via interactive shared book reading (Mol et al 2008). A meta-analysis of parenting education programmes for children aged 3-5 years (Grindal et al 2016) found little beneficial effect unless opportunities to practise parenting skills were provided.…”
Section: Evidence Of the Effectiveness Of Tier 1 Interventionsmentioning
confidence: 99%
“…It is noteworthy that in the 12-month data in this study both the gender balance (favouring girls) and the characteristic social gradient were not clearly demonstrated. Considerable interest in the role of language development has been expressed within a public health context (Law et al 2013, Law andPagnamenta 2017), but the evidence supporting universal interventions is not as strong as that for targeted interventions , but see also McGillion et al 2017 andBlesses et al 2018).…”
Section: Introductionmentioning
confidence: 99%